Mengenalkan Metode 5W+1H dan Melatih Siswa Menulis Caption Instagram di SMA Negeri 12 Palembang - Prisko Adi Saputra; Yeni Ernawati; Yuliana Yuliana (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This activity aims to improve the writing skills of students of SMAN 12 Palembang, especially in composing Instagram captions using the 5W + 1H method. The activity of the Student Creativity Program (PkM) is carried out in the form of counseling and training. the target of counseling and training activities is SMA Negeri 12 Palembang class XI students as many as 34 people. The results of the activity show that students are able to compile informative, relevant, and accurate captions, as well as increase awareness of responsibility in disseminating information on social media. This is expected to be a real contribution in building a responsible literacy culture in the digital era.